EFEKTIVITAS KOMUNIKASI WEBSITE TRIPRIAU.COM SEBAGAI MEDIA INFORMASI PARIWISATA BAGI KOMUNITAS MY TRIP MY ADVENTURE REGIONAL PROVINSI RIAU - ", Nopianah; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The website is a communication media that is not only effective used as a online media provider. One website that is also used as an media provider for various information about tourism in Riau Province. The theory used in this study is the theory of communication effectivity as the main theory and the theory of new media as the supporting theory. The purpose of this study is to find out how much the effectiveness of the Tripriau.com website is as a media for tourism information for the regional community of My Trip My Adventure in Riau Province.This study uses quantitative research methods, with data collection techniques thas is through online questionnaires using google doc to members of the regional My Trip My Adventure community in Riau Province with a total sample of 119 people who were determined through random sampling techniques. The analysis techniques data in this research using descriptive statistical techniques.The results of this research indicate that the level of communication effectivity of Tripriau.com website as a tourism information media for the regional My Trip My Adventure community of Riau Province is classified as effective. This hasbeen proven by the result of collected data that have been measured by six indicators, each of which reaches an average scale of 3.76 on the message receiver (receiver) indicator, a scale of 3.82 on the content message indicator, 3.99 scale on the channel indicator (media), 3.84 scale on the format indicator, 3.93 scale on the message source indicator (source), and a scale of 3.81 on the timekeeping indicator (timing). So the conclusion obtained by using the average formula of all indicators is 3.85 which is included in the effective scale range. This indicates that Tripriau.com website is an effective as a tourism information media for the regional My Trip My Adventure community of Riau Province.Keyword : Communication effectivity , Information, Website, Tourism